2009
DOI: 10.1021/jo8023363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nitroaromatic Peptoids: Fine Tuning Peptoid Secondary Structure through Monomer Position and Functionality

Abstract: N-substituted glycine oligomers, or peptoids, have emerged as an important class of foldamers for the study of biomolecular interactions and for potential use as therapeutic agents. However, the design of peptoids with well-defined conformations a priori remains a formidable challenge. New approaches are required to address this problem, and the systematic study of the role of individual monomer units in the global peptoid folding process represents one strategy. Here, we report our efforts toward this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 29 publications
1
52
0
Order By: Relevance
“…37,39 Analysis of related, small model systems suggested that these structural perturbations arise in part from an interaction between a lone pair of the proximal amide oxygen and a π* orbital of the electron-deficient aromatic ring, that is, an n→π* Ar interaction (also referred to as an lp-π interaction). 40, 41 This type of interaction has been loosely defined by a carbonyl oxygen-to-ring centroid distance between 2.8 and 3.8 Å, and a dihedral angle between the aryl plane and the carbonyl plane (X 2 C=O) of 90° or less.…”
Section: Resultsmentioning
confidence: 99%
“…37,39 Analysis of related, small model systems suggested that these structural perturbations arise in part from an interaction between a lone pair of the proximal amide oxygen and a π* orbital of the electron-deficient aromatic ring, that is, an n→π* Ar interaction (also referred to as an lp-π interaction). 40, 41 This type of interaction has been loosely defined by a carbonyl oxygen-to-ring centroid distance between 2.8 and 3.8 Å, and a dihedral angle between the aryl plane and the carbonyl plane (X 2 C=O) of 90° or less.…”
Section: Resultsmentioning
confidence: 99%
“…32 Therefore, the installation of side chains that are capable of predictably influencing the rotational preferences of the φ and ψ dihedral angles, in addition to the ω dihedral angle, may serve as a general tactic for reducing overall conformational flexibility in polypeptoids. To address these challenges, our group is studying the mechanisms of peptoid folding by probing the effects of various side chain-to-backbone and backbone-to-backbone noncovalent interactions on ω , φ , and ψ dihedral angles in model peptoid systems 3031,3334 We have focused our efforts on monomers that are straightforward to synthesize and install using established peptoid synthesis techniques, thereby enabling their facile incorporation into polypeptoids. Using this fundamental approach, we seek to contribute to a more complete understanding of peptoid sequence-structure relationships, and facilitate the future rational design of peptoids with novel secondary and higher-order structures.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the hydrophobic nature of peptoids compared to the corresponding amino acids they are difficult to crystallize and their structural studies have mainly been carried out by circular dichroism-a low resolution technique and NMR spectroscopy [23,[26][27][28][29][30][31]. Also, crystallographic studies are mostly on cyclic peptoids and there are only a few studies on linear peptoids [32][33][34][35][36]. The amide bond geometry has been reported as cis in N- (1-cyclohexylyethyl) glycine pentamers (in this study DMSO was used as a solvent at the coupling stage and crystals grown from methanol) and trans with N-aryl & N-hydroxyl achiral sidechains (here DMF was the solvent at the coupling stage and crystals grown from CH 2 Cl 2 /n-hexane) [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Also, crystallographic studies are mostly on cyclic peptoids and there are only a few studies on linear peptoids [32][33][34][35][36]. The amide bond geometry has been reported as cis in N- (1-cyclohexylyethyl) glycine pentamers (in this study DMSO was used as a solvent at the coupling stage and crystals grown from methanol) and trans with N-aryl & N-hydroxyl achiral sidechains (here DMF was the solvent at the coupling stage and crystals grown from CH 2 Cl 2 /n-hexane) [32][33][34][35][36][37]. It may also be mentioned that in poly N-methylated α-peptides the amide bond geometry has also been shown to be trans by crystallographic results [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation